The use of some modern techniques in manual therapy and electrical stimulation therapy and their effect on improving chronic pain resulting from cervical disc herniation (Al-Farooq Journal of Sciences, 2026)
The study aimed to investigate the effect of using some modern techniques in manual therapy and electrical stimulation therapy on improving chronic pain resulting from cervical disc herniation and enhancing cervical functional performance. The study adopted the descriptive analytical approach through reviewing scientific literature and previous studies related to the effectiveness of modern physical therapy methods in treating cervical disc herniation and associated chronic pain.The findings revealed that both manual therapy and electrical stimulation therapy played an effective role in reducing pain intensity, improving functional performance, and decreasing muscle spasms among patients. The results also demonstrated that manual therapy contributed more significantly to improving neck flexibility, increasing range of motion, and reducing joint stiffness. In contrast, electrical stimulation therapy was more effective in relieving nerve pain, enhancing muscle and nerve activity, and improving blood circulation within affected tissues.The study further indicated that combining manual therapy with electrical stimulation therapy achieves better therapeutic outcomes compared to using each method separately. This combination was found to accelerate recovery, reduce pain, and improve the quality of life of patients suffering from cervical disc herniation.Accordingly, the study recommended the incorporation of modern physical therapy techniques into treatment plans for patients with cervical disc herniation, while emphasizing the importance of improving physiotherapists’ skills and providing advanced therapeutic equipment in physical therapy centers and hospitals to ensure the best possible therapeutic outcomes.
Keywords: Manual Therapy – Electrical Stimulation – Modern Techniques – Cervical Disc Herniation – Chronic Pain – Cervical Vertebrae – Physiotherapy